PROCESS MANAGEMENT IN A SINGLE INFORMATION FIELD PROVIDING TECHNOLOGI-CAL PROCESSES AT THE AIRPORT - Тамаргазін, Олександр Анатолійович; Ліннік, Іван Іванович (Science-based technologies, 2019)
Many airports in the world face the challenge of increasing their capacity. Airports are experimenting with the use of modern digital technologies. But only a few of them are implementing fundamental digital transformations that can prevent the current difficulties in civil aviation and improve the efficiency of airports. One of the most promising areas of digital transformation of the airport is based on the use of a single information space for technological processes, in which all the works performed at the airport are recorded and controlled. The study showed the need for coordination of decision-making at different levels of airport management, both between different services, departments and airport management, and between airlines and different companies that participate in this airport, in the implementation of technological processes for the maintenance of aviation and ground aviation equipment, passengers, Luggage, cargo, airfield, technical facilities, fuel and lubricants supply system. Such extremely complex technical tasks can be carried out with optimal financial and material costs only when using a single information space at the airport to ensure technological processes. As part of the implementation of this unified information space, it is proposed to implement the methods of "coercion" and "inducement" (pure or combined), which allow the most effective implementation of the potentials inherent in different information resources. One of the important tasks of airport management in this case is to prevent the occurrence of counter-threats from subordinate and dependent structural units and companies, which requires additional costs from persons who make the decision to monitor compliance with the restrictions imposed on technological processes. The use of a single information space to ensure technological processes at the airport allows you to reduce the time to find and implement the optimal actions of the airport management, and thereby reduce the risks of a significant decrease in flight safety in the area of responsibility of the airport.